IMPROVEMENT OF BANK GUARANTEE OPERATIONS IN COMMERCIAL BANKS - Elboev Bobur Batirovich (American Journals, 2024)
This article says that the bank guarantee plays an important role in establishing and strengthening economic relations between partners, developing and developing trade, organizing the production and service process, formalizing various economic contracts, organizing and implementing export-import operations, generating credit relations, participating in tender sales, as well as establishing new cooperation between business entities.
Keywords: Bank, guarantee, bank guarantee, principal, beneficiary, counter - guarantee, financial obligation, invoices.